“Sad Kertih”: Sastra Agama, Filosofi, dan Aktualisasinya - Wiana, I Ketut (Bali Membangun Bali: Jurnal Bappeda Litbang, 2018)
Sad Kerti is six kertis or kertihs (noble behavior) which consists of atma, samudra, wana, danu, jagat, and jana. It is a Hindu concept that is very basic and meaningful and challenging to realize in reality. The six are the basis of this life. Realizing this, the government of Bali, through the new Governor and the new Deputy Governor, has built a comprehensive plan through the paradigm of "Nangun Sad Kerti Loka Bali" which is full of challenges and hopes to build Bali in the next five years. This qualitative article shows that the sad kerti is relevant to be implemented in the development of contemporary Bali that requires its ecological, social and cultural-religious touch. In this way, the well-being of the Balinese people by birth and mind is believed to be achieved as planned. All parties, both the government, the private sector, and the (Balinese) people are actively involved in working together to make it happen.